Measurement of the top quark Yukawa coupling from t(t)over-bar kinematic distributions in the dilepton final state in proton-proton collisions at root s=13 TeV - Sirunyan, A. M. (2020)
A measurement of the Higgs boson Yukawa coupling to the top quark is presented using proton-proton collision data at root s = 13 TeV, corresponding to an integrated luminosity of 137 fb(-1), recorded with the CMS detector. The coupling strength with respect to the standard model value, Y-t, is determined from kinematic distributions in t (t) over bar final states containing ee, mu mu, or e mu pairs. Variations of the Yukawa coupling strength lead to modified distributions for t (t) over bar production. In particular, the distributions of the t (t) over bar mass of the a system and the rapidity difference of the top quark and antiquark are sensitive to the value of Y-t. The measurement yields a best fit value of Y-t = 1.16(-0.35)(+0.24), bounding Y-t < 1.54 at a 95% confidence level.